Resíduos e subprodutos agroindustriais e grãos como substratos para produção do fungo entomapatogênico Lecanicillium lecanii - Machado, Ana Carolina Ribeiro [UNESP]; Monteiro, Antonio Carlos [UNESP]; Mochi, Dinalva Alves [UNESP]; Yoshida, Luciana [UNESP] (Instituto Agronômico de Campinas, 2009)
Lecanicillium lecanii é um fungo promissor no controle biológico de pragas e para sua utilização em campo é necessária a produção de conídios em grande quantidade. Este trabalho objetivou selecionar meios de cultura líquidos feitos com resíduos ou subprodutos agroindustriais e meios sólidos pela mistura de grãos e derivados, visando à produção dos isolados JAB 02 e JAB 45 do fungo. Como substratos líquidos utilizaram-se, em diferentes concentrações, água do cozimento do arroz e da prensa da mandioca, soro de queijo, milhocina®, melaço, vinhaça e leite de levedura da indústria da cana, avaliando-se a esporulação e biomassa. Como substratos sólidos, combinaram-se, em diferentes proporções, trigo grosso, farelos de trigo e de soja com quirela de milho, lentilha e sorgo para JAB 02, e com painço, trigo em grão e lentilha para JAB 45, avaliando-se a produção e viabilidade de conídios. O meio contendo 4% de milhocina® favoreceu a produção de ambos os isolados. Para JAB 02, proporcionaram melhores resultados os meios com 85% de água da prensa da mandioca, 5,5% de melaço e 100% de soro de queijo, além de misturas entre trigo grosso e farelo de trigo com lentilha (70:30%) e trigo grosso e farelo de trigo com sorgo (85:15%). Os meios com 100% da água da prensa da mandioca e 85% de soro de queijo, e as misturas entre farelo de trigo e painço (85:15%), trigo grosso e lentilha (55:45%) e farelo de trigo com trigo em grão e com lentilha (70:30%) favoreceram a produção de JAB 45.

Lecanicillium lecanii is a fungus that shows much promise as a biological control agent against plague. To explore this possibility in field conditions conidia would have to be produced in large scale. With this dim, the present study selected substrates that could be used as media for cultivating isolates JAB 02 and JAB 45 from this fungus. Liquid media prepared with agro industrial by-products and residue, and solid media using mixtures of grain and derivates were tested. For liquid media different concentrations of water obtained from cooking rice and from squeezing dry cassava root, besides cheese whey , milhocina®, sugar cane molasses, vinasse and cream yeast from sugar cane milling, were assessed regarding spore production and biomass. Considering solid media, ground wheat, wheat and soy brans with broken corn, lentil seed and sorghum were all combined in different proportions for JAB 02, and with millet seed, wheat grain and lentil seed for JAB 45. These were assessed regarding conidia productivity and viability. The medium containing 4% milhocina® promoted good productivity from both isolates. Regarding JAB 02, the substrates containing 85% water from the squeezed cassava, 5,5% of molasses and 100% cheese whey, besides the mixtures of ground wheat and wheat bran with lentil seed (70:30%) and ground wheat and wheat bran with sorghum (85:15%) produced the best results. The media containing 100% water from the squeezed cassava with 85% cheese whey; and the mixtures of wheat bran plus millet seed (85:15%); ground wheat and lentil seed (55:45%); and wheat bran with wheat grain plus with lentil seed (70:30%) favored productivity in the JAB 45 isolate.
Grain and agroindustrial residue and by-products as substrate for production of the Lecanicillium lecanii entomopathogenic fungus
Keywords: Biological control; Mass production; liquid substrates; solid substrates; Controle biológico; Produção massal; substratos líquidos; substratos sólidos